Public participation in constitution-making : a critical assessment of the Kenyan experience - Fessha, Yonatan Tesfaye (University of Pretoria, 2010)
A dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Dr. Yonatan Tesfaye Fessha, Unversity of Western Cape, South Africa.